Plan estratégico para la unidad educativa Los Guayacanes, cantón Quevedo, periodo 2014-2017 - Naranjo Verduga, Rosa Elena (2015)
This thesis project was developed for Educational Unit "Los Guayacanes", and its problematic lack of a strategic plan in this organization, for which proposed the development and implementation applicable during the period 2014-2017. To achieve the above-described information it was collected through primary and secondary sources. The obtained data from interviews and surveys undertaken, to the conclusion that the Education Unit "Los Guayacanes is an institution recognized in the environment in which it operates, who despite having an Institutional Educational Project and the support of a right talent has failed to get the expected returns by senior management, which is why the need for the development of a strategic plan for the institution arises, containing the same improvement projects necessary to achieve the success of the organization whole. Regarding the research design, the theoretical framework was developed based on the establishment of concepts derived from the research topic, these being taken from books and the Internet. Such as research methods were also used: analytical, inductive, deductive and descriptive method, which made the development of research as possible; meanwhile the research techniques used were interviews, surveys and direct observation technique, through which it….